Aspirin in combination with gastrodin protects cardiac function and mitigates gastric mucosal injury in response to myocardial ischemia/reperfusion - Dong, Zhiwu; Yang, Lin; Jiao, Jianlin; Jiang, Yongliang; Li, Hao; Yin, Gaosheng; Yang, Ping; Sun, Lin (Frontiers in Pharmacology, 2022)
Myocardial ischemia/reperfusion (I/R) injury after percutaneous coronary intervention (PCI) is common in patients with acute myocardial infarction. Aspirin is the commonly prescribed antithrombotic therapy for patients with coronary heart disease (CHD). However, long-term use of aspirin causes severe gastric mucosal damage. Gastrodin is a natural medicine used in Traditional Chinese Medicine (TCM) with anti-inflammatory and anti-oxidative properties. In this study, we investigated the effects of combined therapy with aspirin and gastrodin on the myocardial and gastric mucosal injury in response to myocardial I/R injury and the underlying mechanisms using the Sprague-Dawley rat model. Our results demonstrated that myocardial I/R caused significant cardiac dysfunction and gastric mucosal damage. Aspirin significantly reduced myocardial infarction size and cardiomyocyte death and enzyme release, and significantly improved cardiac function through anti-inflammatory. However, aspirin exacerbated gastric mucosal damage by increasing the levels of inflammatory mediators and endothelin (ET) and reducing prostaglandin E2 (PGE2) levels. The combined treatment with aspirin and gastrodin significantly protected gastric mucosa by normalizing the expression levels of the inflammatory factors, ET, and PGE2. The combined treatment with aspirin and gastrodin significantly reduced myocardial infarction size, cardiomyocyte death, and improved cardiac function by inhibiting inflammation in response to I/R. The combination therapy also significantly reduced the levels of pyroptosis-related proteins in the myocardium and the gastric mucosa. The combination therapy showed significantly reduced level of thromboxane B2 (TXB2). Moreover, the combination treatment showed increased levels of the tissue plasminogen activator (t-PA). This suggested that gastrodin did not inhibit the anti-thrombotic functions of aspirin. Accordingly, aspirin in combination with gasrtodin protected the structural and functional integrity of the heart and the stomach by suppressing pyroptosis and inflammation. Therefore, combination of aspirin and gastrodin is a promising treatment for cardiac dysfunction and gastric mucosa injury after myocardial I/R.